Pemanfaatan Tutup Botol Plastik Menjadi Keychain Character - Susilawati Susilawati; Nabila Athiya Zulfa; Dela Amelia; Safira Ayu Ningtias; Uyun Saskiyah (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Plastic bottle caps are a commonly discarded household waste despite their potential for reuse due to the thermoplastic properties of HDPE and PP materials. These plastics can be reshaped when heated, allowing them to be transformed into functional and aesthetic products. This activity aimed to apply the principles of the 3R concept particularly reuse and recycle by converting discarded bottle caps into character-themed keychains. The process involved several stages, including material collection, heating with an iron using baking paper as a barrier, molding with silicone forms, trimming, and assembling the keychain components. Thermoforming was selected as the primary technique because it is simple, safe, and compatible with the behavior of thermoplastic materials that soften under moderate heat. The results indicate that bottle caps can be successfully reshaped into durable and visually appealing keychains. Beyond producing a functional product, the activity enhanced creativity, manual skills, and environmental awareness regarding plastic waste utilization. Thus, converting bottle caps through thermoforming demonstrates a practical upcycling approach that reduces waste generation while producing items with functional and economic value.